Ionic liquids for Topical Delivery in Cancer - Dias, Ana Rita (2019)
The unique properties of ionic liquids make them quite appealing for diverse applications, from "green" solvents (1st generation ionic liquids) to finely tuned materials (2nd generation ionic liquids). A decade ago, a 3rd generation of ionic liquids emerged which is focused on their prospective clinical applications, either as drugs per se or as adjuvants in drug formulations. In recent years, research focused on use of ionic liquids for topical drug delivery has been increasing and holds great promise towards clinical application against skin cancers. This article highlights the growing relevance of ionic liquids in medicinal chemistry and pharmaceutical technology, which is opening new windows of opportunity.